2018
DOI: 10.1088/1361-6463/aadfab
|View full text |Cite
|
Sign up to set email alerts
|

Screening and engineering of colour centres in diamond

Abstract: We present a high throughput and systematic method for screening of colour centres in diamond. We aim at the search and reproducible creation of new optical centres, down to the single level, potentially of interest for the wide range of diamond-based quantum applications. The screening method presented here should moreover help identifying some already indexed defects among hundreds in diamond [1] but also some promising defects of still unknown nature, such as the recently discovered ST1 centre [2,3]. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
97
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(120 citation statements)
references
References 109 publications
20
97
3
Order By: Relevance
“…Qubits in diamond based on the nitrogen-vacancy (NV) centre are widely implemented for a large range of applications like quantum information processing 1 , quantum sensing of magnetic fields 2 , electric fields 3 , or temperature 4 but also for nuclear magnetic resonance 5 or even to answer fundamental questions in physics 6,7 . The fabrication and reproducibility of scalable devices requires (and still lacks) sample homogeneity and creation yields of the qubits close to 100% 8 , but as well, the control and engineering of their environment 9 . The addressing using ion implantation provides high spatial resolution 10 , placement accuracy 11 , and even deterministic countable single ions 1215 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qubits in diamond based on the nitrogen-vacancy (NV) centre are widely implemented for a large range of applications like quantum information processing 1 , quantum sensing of magnetic fields 2 , electric fields 3 , or temperature 4 but also for nuclear magnetic resonance 5 or even to answer fundamental questions in physics 6,7 . The fabrication and reproducibility of scalable devices requires (and still lacks) sample homogeneity and creation yields of the qubits close to 100% 8 , but as well, the control and engineering of their environment 9 . The addressing using ion implantation provides high spatial resolution 10 , placement accuracy 11 , and even deterministic countable single ions 1215 .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that a large part of these vacancies are lost by recombination with carbon interstitials, by formation of di-vacancies or other complexes (vacancy chains, VH) or by diffusion to dislocations or to the diamond surface for the shallow ones. It was moreover shown that the proportion of vacancy complexes (with respect to isolated vacancies) increases with the atomic mass of the implanted ions 9 and that suitable thermal treatments enable the dissociation of vacancy chains 21 . Efforts were also made to increase the NV yield (for example by co-implantation of carbon 22 , post-irradiation with electrons or protons to produce additional vacancies 23,24 or more recently very efficiently by laser writing 25 ) and to understand the NV formation process 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…3,9 However, because diamond has a very large band gap this provides opportunities for the use of alternate optically active defects. [10][11][12] In this context, both the Si-and Ge-vacancy defect have received increased interest. [13][14][15][16][17] Within condensed matter science, rare-earth (RE) elements receive a lot of attention as optical dopants, as they give rise to very sharp emission lines, for a wide variety of wavelengths from UV to IR.…”
Section: Introductionmentioning
confidence: 99%
“…Both NV PL quenching as well as enhancement has been reported in the literature over a wide range of temperatures from 1100-1500 • C [38][39][40][41], with higher tem-perature quenching often attributed to NV migration to form larger complexes [41,42]. Due to short N migration length, complex formation can only explain quenching in high-N samples [25]. Our results indicate several factors may account for the observed variance in NV quenching: (1) Compositional sample variance with respect to hydrogen traps, (2) Simultaneous creation and quenching events with the specific annealing temperatures and times determining a net outcome in either direction and (3) the hydrogen content in the annealing furnace, suggested by our observed surface dependence of the depletion layer.…”
Section: Discussionmentioning
confidence: 99%